A complex network analysis of inbound tourism in Sicily. (12th December 2019) - Provenzano, Davide; Baggio, Rodolfo
Abstract: In this article, the complex dynamics of inbound tourism in Sicily is analyzed for the period 1998–2017. The horizontal visibility graph algorithm is used to transform the overnight stays' time series into a network whose topology is investigated by standard network analysis. Discontinuities in the domestic and international tourism demand were identified in order to detect signals of change and the timing of the directional change in tourism growth. The network degree distribution confirms the complex structure of the destination and reveals the random and thus more unpredictable nature of the international tourism demand in Sicily, compared with a more stable domestic segment. Some policy implications are drawn.